(untitled) (Journal of Partial Differential Equations, 2021)
"In the present paper we study the well-posedness using the Galerkin method and the stabilization considering multiplier techniques for a fourth-order nonlinear Schr00f6dinger equation in domains with moving boundaries. We consider two situations for the stabilization: the conservative case and the dissipative case."